Comparing the Effectiveness of Biodiversity Conservation Across Different Regions by Considering Human Efforts - Dong, Kaikai; Liu, Zhaoli; Li, Ying; Chen, Ziqi; Hou, Guanglei; Sun, Jingkuan (Frontiers in Ecology and Evolution, 2022)
The effective allocation of funds is of significant importance for biodiversity conservation, but there is currently no scientific method for comparing the effectiveness of biodiversity conservation across different regions. Existing studies omit differences in the ecological background, such as the terrain, climate, hydrology, soil, and ecosystem, or do not differentiate between the impacts caused by humans and nature. To address these limitations, we take habitat quality as a proxy for biodiversity and quantify the human-induced habitat quality changes as a means of measuring the efforts of management departments, with the background differences eliminated using a reference condition index. The method is applied to the San Jiang Plain Wetlands and Northwest Tibet Qiang Tang Plateau Biodiversity National Key Ecological Function Region in China. The results show that the effects of human activities on habitat improvement or degradation are overestimated or underestimated if there is no differentiation between human and natural causes. Human-induced habitat quality changes broadly reflect the human efforts towards biodiversity conservation. By considering the human efforts and background differentiation, the proposed method allows the effectiveness of biodiversity conservation to be compared across different regions. This study provides a scientific reference for China’s transfer payment policy and for the biodiversity funds allocated in other countries. Furthermore, our results will guide the practice of improving habitat quality and biodiversity.